Pakistan: Breaking Barriers Through Special Education - Miles, M. (Journal of religion, disability & health, 2002)
The paper outlines some of the social barriers and difficulties facing disabled children in the North West Frontier Province of Pakistan in the 1980s. It describes how some people working with the Church of Pakistan, Diocese of Peshawar, began offering special education, in collaboration with interested Muslim teachers and social workers, and also initiated the extension of services by mobilising local Muslim community organisations in other towns to start their own work with disabled children.